Cattle Drive Salmonella Infection in the Wildlife–Livestock Interface. (17th December 2012) - Mentaberre, G.; Porrero, M. C.; Navarro‐Gonzalez, N.; Serrano, E.; Domínguez, L.; Lavín, S.
Summary The genus Salmonella is found throughout the world and is a potential pathogen for most vertebrates. It is also the most common cause of food‐borne illness in humans, and wildlife is an emerging source of food‐borne disease in humans due to the consumption of game meat. Wild boar is one of the most abundant European game species and these wild swine are known to be carriers of zoonotic and food‐borne pathogens such as Salmonella. Isolation of the pathogen, serotyping and molecular biology are necessary for elucidating epidemiological connections in multi‐host populations. Although disease management at population level can be addressed using a number of different strategies, such management is difficult in free‐living wildlife populations due to the lack of experience with the wildlife–livestock interface. Herein, we provide the results of a 4‐year Salmonella survey in sympatric populations of wild boar and cattle in the Ports de Tortosa i Beseit National Game Reserve (NE Spain). We also evaluated the effects of two management strategies, cattle removal and increased wild boar harvesting (i.e. by hunting and trapping), on the prevalence of the Salmonella serovar community. The serovars Meleagridis and Anatum were found to be shared by cattle and wild boar, a finding that was confirmed by 100% DNA similarity patterns using pulse field gel electrophoresis. Cattle removal was more efficient than the culling of wild boar as a means of reducing the prevalence of shared serotypes, which underlines the role of cattle as a reservoir of Salmonella for wild boar. To our knowledge, this is the first attempt to manage Salmonella in the wild, and the results have implications for management.